Infographics for dummies - Beegel, Justin, ....- (Hoboken, N.J. : John Wiley & Sons, 2014)
Discover visual marketing with infographics, tips on designing and distributing great infographics, how to make your work shareable, and much more. Beegle gives you a complete overview of the field, and helps you discover how to create and distribute your own.
Includes index.
Keywords: Communicatie -- Grafische methodes; Communication -- Graphic methods; Information visualization; Presentation graphics software; Visual communication; Visuele communicatie